2014
DOI: 10.1038/srep04721
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modulation of the Biological Activity of Reutericyclin: a Membrane-Active Antibiotic from Lactobacillusreuteri

Abstract: Whilst the development of membrane-active antibiotics is now an attractive therapeutic concept, progress in this area is disadvantaged by poor knowledge of the structure-activity relationship (SAR) required for optimizing molecules to selectively target bacteria. This prompted us to explore the SAR of the Lactobacillus reuteri membrane-active antibiotic reutericyclin, modifying three key positions about its tetramic acid core. The SAR revealed that lipophilic analogs were generally more active against Gram-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Against Enterococcus faecalis and methicillin-resistant S. aureus (MRSA), most hybrids had MICs >25 µg/ml. Previously, we reported that the antimicrobial activity of tetramic acids belonging to the membrane active reutericyclin class was influenced by hydrophobic substituents at the N1, C5, and 3-positions of the tetramic core and that the simple hydrophilic tetramic acid core alone did not possess measurable antibacterial activity (MICs > 200 µg/ml) against Gram-positive bacteria [18, 34]. In comparison, for tetramic acid-ampicillin hybrids, different substituents at the C5 and N1-positions on the tetramic core, irrespective of their size, shape, hydrophobicity, and polarity produced similar activity, and no clear SAR was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Against Enterococcus faecalis and methicillin-resistant S. aureus (MRSA), most hybrids had MICs >25 µg/ml. Previously, we reported that the antimicrobial activity of tetramic acids belonging to the membrane active reutericyclin class was influenced by hydrophobic substituents at the N1, C5, and 3-positions of the tetramic core and that the simple hydrophilic tetramic acid core alone did not possess measurable antibacterial activity (MICs > 200 µg/ml) against Gram-positive bacteria [18, 34]. In comparison, for tetramic acid-ampicillin hybrids, different substituents at the C5 and N1-positions on the tetramic core, irrespective of their size, shape, hydrophobicity, and polarity produced similar activity, and no clear SAR was observed.…”
Section: Resultsmentioning
confidence: 99%
“…reutericyclins) are typically inactive against the Gram-negative test panel in Table 2 [15, 18, 34]. However, against the panel of type strains of gram-negative bacteria, fusion of ampicillin with tetramic acid produced variable effects against the different species (Table 2), with a general observed trend that some hybrids showed increased activity over ampicillin and carbenicillin, but were inferior to piperacillin for some key species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to the tetramic acid (TMA) compound class that includes diverse natural products such as reutericyclin active against Gram-positive pathogens including staphylococci, clostridia and streptococci 13–15 . The cellular targets of the antibacterial TMAs range from cell wall biosynthesis, DNA topoisomerase and RNA polymerase to membrane potential 15 . 5HE-C10-TMA in common with reutericyclin dissipates the cytoplasmic membrane potential and pH gradient, and is an iron(III) chelator 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Initially, given the highly lipophilic nature of the parent compounds and their structural similarities with antibiotics such as the reutericyclins, we sought to explore the effect of these compounds on membrane integrity. [28] We subjected the compounds to a red blood cell hemolysis assay (defibrinated sheep blood), [29] revealing less than 1% hemolysis at 40 μM for both natural product 1 and compound 29 . Furthermore, a BacLight ™ assay was utilized with S. aureus ATCC 29213 to evaluate the membrane permeabilization.…”
mentioning
confidence: 99%